Shaping Destinies: Women and the Hungarian Refugee Movement to Canada (1956–1958) - Trimble, Sheena (Hungarian Journal of English and American Studies, 2022)
By December 1958, Canada had admitted almost 38,000 Hungarian refugees, forced to flee their country after Soviet forces crushed the October 1956 uprising. A rich historiography has examined this migration from a range of perspectives, but an analysis of women’s actions and attitudes represents an uncharted approach. Archival research reveals that Canadian women expressed opinions and took on a variety of roles related to the refugee movement. Examining those opinions and roles not only offers a novel perspective on Canada’s response to the refugee crisis, but it also provides insights into the evolving roles of women in Canadian society. The weight of intersectionality often muted the voices of women of Hungarian origin, both Canadians and refugees. Yet, refugee women were accorded a symbolic power that played its own role in the movement, and they found ways to exercise their agency to achieve their desired admission and settlement outcomes. (ST)